1998
DOI: 10.1042/bj3370037
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic triad of microsomal epoxide hydrolase: replacement of Glu404 with Asp leads to a strongly increased turnover rate

Abstract: Microsomal epoxide hydrolase (mEH) belongs to the superfamily of alpha/beta-hydrolase fold enzymes. A catalytic triad in the active centre of the enzyme hydrolyses the substrate molecules in a two-step reaction via the intermediate formation of an enzyme-substrate ester. Here we show that the mEH catalytic triad is composed of Asp226, Glu404 and His431. Replacing either of these residues with non-functional amino acids results in a complete loss of activity of the enzyme recombinantly expressed in Saccharomyce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
16
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…Moreover, it has been reported that Asp226, Glu404 and His431 constitute the EPHX1 catalytic triad. The Asp226 residue attacks the oxirane ring to yield an alkylenzyme intermediate, which is followed by subsequent hydrolysis with water activated through proton abstraction by Glu404 and His431 residues (Arand et al 1999). Together with these latter residues, the non-synonymous change at the residue 43 might exert an influence on the catalytic activity or the conformational structure of the active site.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, it has been reported that Asp226, Glu404 and His431 constitute the EPHX1 catalytic triad. The Asp226 residue attacks the oxirane ring to yield an alkylenzyme intermediate, which is followed by subsequent hydrolysis with water activated through proton abstraction by Glu404 and His431 residues (Arand et al 1999). Together with these latter residues, the non-synonymous change at the residue 43 might exert an influence on the catalytic activity or the conformational structure of the active site.…”
Section: Discussionmentioning
confidence: 99%
“…On the contrary, M. cephalus EH has glutamic acid (E378). Based on this feature, we can expect that the hydrolysis rate can be increased by changing the E378 to aspartate because the pK a value of aspartic acid is smaller than that of glutamic acid (Arand et al 1999).…”
Section: Replacement Of Glutamate By Aspartate In Charge-relay Systemmentioning
confidence: 97%
“…Because the activation energy required for the hydrolysis of ester intermediate is higher than that for ester formation, the second step is the slow rate-limiting step (Arand et al 2003). Based on this feature, the hydrolysis rate could be increased by replacing the Glu to Asp because the pK a value of Asp is smaller than that of Glu (Arand et al 1999). …”
Section: Epoxide Hydrolase: Structure and Catalysismentioning
confidence: 98%